2012
DOI: 10.1021/bc200525x
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic Acid Supported Si–18F-Radiofluorination: One-Step Radiosynthesis of N-Succinimidyl 3-(Di-tert-butyl[18F]fluorosilyl)benzoate ([18F]SiFB) for Protein Labeling

Abstract: N-Succinimidyl 3-(di-tert-butyl[(18)F]fluorosilyl)benzoate ([(18)F]SiFB), a novel synthon for one-step labeling of proteins, was synthesized via a simple (18)F-(19)F isotopic exchange. A new labeling technique that circumvents the cleavage of the highly reactive active ester moiety under regular basic (18)F-labeling conditions was established. In order to synthesize high radioactivity amounts of [(18)F]SiFB, it was crucial to partially neutralize the potassium oxalate/hydroxide that was used to elute (18)F(-) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…The recent implementation of the “Munich method” alongside the SiFA-IE labeling approach for peptide and protein labeling [43, 46, 58, 59] offers unique and unequalled simplicity, where, starting from commercially available [ 18 F]F − /[ 18 O]H 2 O, it is possible to deliver [ 18 F]SiFA radiopharmaceuticals using only room temperature transformations and facile cartridge-based manipulations. Following this approach, the 18 F-labeling of complex unprotected biomolecules becomes almost as easy as using a 99m Tc-kit.…”
Section: Towards a Kit Formulation For Sifa-iementioning
confidence: 99%
“…The recent implementation of the “Munich method” alongside the SiFA-IE labeling approach for peptide and protein labeling [43, 46, 58, 59] offers unique and unequalled simplicity, where, starting from commercially available [ 18 F]F − /[ 18 O]H 2 O, it is possible to deliver [ 18 F]SiFA radiopharmaceuticals using only room temperature transformations and facile cartridge-based manipulations. Following this approach, the 18 F-labeling of complex unprotected biomolecules becomes almost as easy as using a 99m Tc-kit.…”
Section: Towards a Kit Formulation For Sifa-iementioning
confidence: 99%
“…9 Precursor 17a and 17b were prepared as reported by Kostikov (Scheme 3). 25,26 Compounds 12a and 12b were synthesized by nucleophilic substitution of di-tert-butyldifluorosilane and ditert-butylchlorosilane respectively, starting from the reaction between ((3-bromobenzyl)oxy)(tert-butyl)dimethylsilane and tertBuLi. Acidic deprotection afforded compounds 13a and 13b in good yields.…”
Section: Chemistrymentioning
confidence: 99%
“…The copper(I)-catalyzed cycloaddition of azides with terminal alkynes to form 1,2,3-triazole has proved to be particularly valuable for efficient 18 F labeling of biomolecules. Ramenda et al has reported 18 F-labelled sulfonamide-based click chemistry building blocks to radiolabel HAS [21], A non-conventional Si- 18 F bonded prosthetic group has also been used to radiolabel serum albumin [22], [23]. In this approach a prosthetic group for non-site-specific protein labeling was designed and synthesized in one step by simple 19 F– 18 F isotopic exchange.…”
Section: Introductionmentioning
confidence: 99%